SUNGKAN, A JAVANESE CULTURAL TRAIT AND THE WILLINGNESS TO SPEAK (WTS) AMONG JAVANESE LEARNERS OF ENGLISH - B. Agus Darwanto (Conscientia, 2022)
This research was intended to examine if a Javanese cultural trait “sungkan” affects students’ willingness to speak (WTS) in English. Questionnaires of closed and open-ended questions were distributed to obtain information around sungkan and its association with WTS from 12 lecturers (the group of seniors) and 15 college students of English (the group of juniors). The amount of sungkan and WTS in English in different speaking events was determined. The results, first, show that unlike the juniors, the seniors still dearly hold sungkan. When fronted with events that signified the importance of the practice of sungkan, the senior repondents outperformed the juniors in adhering to the cultural trait. Second, for both groups, sungkan proves to affect their WTS in L2 (English) especially with the seniors, the well-acquainted speaking partners, and the people of power. The more distant the status is, the more sungkan is observed and if less or no personal identification is detected, less sungkan is pronounced and the WTS in L2 (English) increases. In conclusion, the rate of sungkan correlates with the level of WTS among these Javanese learners of English.